Effect of rotation of feed and seed rods on the quality of Na0.75CoO2 single crystal grown by traveling solvent floating zone method - Sekar, C.; Paulraj, S.; Kanchana, P.; Schüpp-Niewa, B.; Klingeler, Rüdiger; Krabbes, G.; Büchner, B. (Materials research bulletin, 2011)
High purity Na0.75CoO2 single crystals have been grown by floating zone method. We found the rotation of feed and seed rods play a crucial role in growing high quality single crystal. Systematic investigations suggest the occurrence of a phase separation at microscopic level, such as the separation into Na-rich and Na-poor domains during the growth, and formation of impurity phase(s) depending on growth conditions. NaxCoO2 (x=0.30, 0.60) crystals have been prepared by sodium deintercalation from Na0.75CoO2. Powder X-ray and energy dispersive X-ray analyses have confirmed the phase purity and homogeneity of the samples. Magnetic susceptibility measurements of x=0.60 and 0.75 crystals indicate a bulk phase transition at 22K and an anomaly around 339K and 334K respectively which are attributed to structural transition. In addition some unique features related to Na0.60CoO2 were observed.
Die Ziffern 0.75 und 2 sind im Titel tiefgestellt
Gesehen am 23.11.2022